The Views of School Administrators toward Issues of School Siting: A Geographical Analysis - Sağdıç, Mustafa; Demirkaya, Hilmi (Journal of History Culture and Art Research, 2019)
The purpose of this study is to examine the views of school administrators with respect to school siting, conducted by themselves, by means of geographical perspectives in İstanbul province. This qualitative research was designed as a phenomenological study. Data were collected via individual semi-structured interview form that was developed by the researchers based on the literature review, expert opinions, and pilot study. Content analysis method was applied while assessing the interview records. Depending on the findings obtained through an open-ended questionnaire, the following categories are formed; a) Positive Themes: (1) Safe environment, (2) Easy transportation and large school playground and (3) Socially-favorable environment, b) Negative Themes: (1) High risk of natural disaster, (2) Intensive urbanization and insufficient schoolyard, (3) Wrong location selection, (4) Unsuitable social environment and (5) Transportation problems. Therefore, findings from this research are expected to encourage the Turkish government, especially the Ministry of National Education, to develop and create a guideline for the safe school environment in Turkey.